Teachers' Initiated Ways in Handling Teenage Pregnancy Cases - Gomez, Lourdes; Omandam, Mary Jane B. (Papanda Publisher, 2023)
Teenage pregnancy is a severe problem that causes drop-outs of females and decreases enrollment for the next school year. School administrators implement and extend academic support to help teenage mothers in their education. The purpose of this qualitative single case study was to describe the experiences of secondary teachers in handling pregnant learners and teenage mothers for School Year 2021-2022 until SY 2022-2023. The researcher interviewed eight secondary teachers with teenage pregnant learners, and teenage mothers under their class advisory was chosen through purposive sampling. In-depth interviews, observations, and field notes were utilized in the gathering of data. Using categorical analysis of the results, the secondary teachers' practices in handling this case focused on how teachers reacted to the situation, challenges that teachers encountered, teachers-initiated ways, academic support, and teenage mothers' response to the support they extended to them. Teachers described their experiences in handling pregnancy cases from the participants' utterances: Processing of mixed emotions and concern with the long-term welfare of students. Teachers need to gain a background in counseling and students' absenteeism with late submission of learning sheets. Having In-depth Conversations, Using ICT in reaching out to students, Giving Financial and Kind Support to students, and Providing Arrangement of Supplemental Activities to Students. They were giving school supplies to students, shifting to a blended learning modality, and conducting home visits / future home visits. Positivity and Keeping Academic Interest are the expected response of teenage mothers toward the academic support extended to them. According to the results, regardless of marital status of secondary teachers, their approaches in handling teenage pregnancies and mothers varied depending on the student's situation following the same strategies and techniques applied. Positive outcomes are produced on the parts of teachers and students when school administrators provide affected students with academic support.